Analysis of ability to use microscope and its relation with visual and verbal representation in representing microscopic objects in anatomy of plant lecture. Issue 2 (February 2019) - Widodo, E; Rahmat, A; Nuraeni, E
Abstract: Visual representation is a person's ability to represent objects visually while verbal representation is a person's ability to represent objects in writing or oral. This study aims to identify the ability to use a microscope and its relation to the visual and verbal representation of students in representing microscopic objects in anatomy of plant lecture. The type of research used in this research is descriptive research. Research subjects are Biology Education students who register the subject of plant anatomy. The instruments used are general visual and verbal ability's tests, microscope usage rubrics, visual and verbal assessment rubrics, and questionnaires. At the beginning of the lecture 51% of students have the ability to use microscopes in the category of poor. After 5 lecture meetings, the students' ability to use microscope increased to 60% in the category of good. The ability to use microscope is correlated with students' ability to represent objects visually (visual representation) (r = 0.373; p < 0.05) and verbally (verbal representation) (r = 0.669; p < 0.01). The result shows that the ability to use a microscope is not the only factor that contributes to the student's ability to represent microscopic objects both visually and verbally. Several contributing factors are discussed in this paper.